Ice age [videorecording (DVD)] - Wedge, Chris, 1958-; Romano, Ray; Leguizamo, John; Leary, Denis (Twentieth Century Fox Home Entertainment, 2002)
A band of creatures fleeing the coming ice age tries to reunite a human baby with it's tribe.